A institucionalização da Lei nº 14133/2021 na Grande Aracaju: desafios e perspectivas para a gestão pública municipal - Braga, Martha Elizabeth Araújo de Mendonça (2025)
Objective: This study aimed to analyze the stage of institutionalization of Law No. 14.133/2021 in the municipalities of Greater Aracaju, identifying the mechanisms, regulatory patterns, and implementation from an institutional efficiency perspective. Methodology: A qualitative and descriptive approach was adopted, with methodological procedures including document analysis, semi-structured interviews with public officials, and analysis of data collected from the municipalities' electronic portals. The research was guided by Ostrom's Theory, applying categories such as monitoring, sanctions, and shared responsibility to understand the institutionalization of the new legislation. Key Findings: The results indicate that the municipalities in Greater Aracaju face significant challenges in implementing Law No. 14.133/2021, such as lack of staff training, cultural resistance, and insufficient technological resources. Despite these challenges, specific initiatives aimed at adapting to the new legislation were identified, particularly in the use of digital tools and the planning of contracts. Theoretical and Methodological Contributions: Theoretically, the study contributes by broadening the understanding of the institutionalization of legislative reforms in local contexts, reinforcing the applicability of Ostrom’s Theory to public management. Methodologically, it provides a practical approach to analyzing institutional maturity in the context of implementing new regulations. Relevance and Originality: The study is relevant as it addresses a contemporary and crucial issue for the modernization of public administration in Brazil. Its originality lies in the application of a well-established theoretical approach, such as Ostrom’s Theory, to the specific context of Greater Aracaju, offering new perspectives for the study of public governance. Social and Managerial Contributions: Socially, the study highlights the importance of training public officials and strengthening practices that promote transparency and efficiency in public management, directly benefiting society. In terms of management, it suggests monitoring strategies and incentive mechanisms for the effective adoption of the new legislation, contributing to improvements in the bidding and contracting processes in the municipalities analyzed.